On the performance of TCP pacing with DCCP - Awang Nor, Shahrudin; Hassan, Suhaidi; Ghazali, Osman; Che Mohamed Arif, Ahmad Suki (2010)
Packet pacing in TCP has been introduced as one of the solutions to alleviate bursty traffic in TCP.In this paper, we investigate the performance of paced and standard (unpaced) TCP when coexist with DCCP over short and long delay link networks.We found that paced TCP for the entire TCP connection performs better in long delay link, with smoother throughput and better jitter, whereas in short delay link, there is not much positive effect of using pacing for TCP. The existence of DCCP together with TCP flows does not much affect the performance of paced TCP.However, the performance of paced TCP is slightly better when coexisting with DCCP TCP-like and DCCP TFRC in comparison to standard TCP.Based on the result, it can be used as a fundamental in implementing packet pacing in DCCP TCP-like.